Formation of a monitoring system for trend signals in the organisation of the marketing information support process - Churlei, Eduard G. (Journal of the Belarusian State University. Economics, 2021)
Changes in the competitive field and the speed of the course of events orient market players to the need to search for trend signals and analyse trends. Relevant methods are the monitoring of secondary resources, expert methods and the using models to reflect the qualitative and quantitative research results and trend analysis.